Towards a Strategy for Manufactured Exports to Japan - Peter Lee U; Ferdinand Maquito (Philippine Institute for Development Studies (PIDS), 2004)
The Philippines has become an export-oriented economy, with exports increasing in significance. The electronics industry, in particular, is a showcase of this newfound export prowess. Traditionally, comparative advantage is the takeoff point for understanding trade patterns in economic theory. This paper tries to augment the static nature of the theory of comparative advantage with the dynamics of the flying geese model of economic growth. Applied to the context of Japanese manufacturing networks in recent years, it provides an understanding of the flow of Japanese investments overseas. Export processing zones or special economic zones seem to have played an important role in the electronic industry's export success by attracting sizable investments. This paper estimates an export output production function for special economic zones in the Philippines and finds that most exhibit constant if not increasing returns to scale. It also finds that export output tends to be elastic with respect to labor input in most cases. This lends support to interview findings that cite the quality of labor as an attraction of the Philippines. The paper also points out that rates of domestic procurement by Japanese manufacturing firms remain low, suggesting poor backward integration with the rest of the economy. Lastly, the paper ends with some comments and suggestions on the existing draft of the Japanese Philippine Economic Partnership Agreement available at the time of writing.
Keywords: 330; comparative advantage; Japan-Philippines economic partnership; export processing zone; export strategy; flying geese model; Außenhandel mit Industriegütern; Internationale Wirtschaftsbeziehungen; Philippinen; Japan; Fluggänsemodell